Clinical practice guidelines for rehabilitation in traumatic brain injury: a critical appraisal. (24th August 2019) - Lee, Su Yi; Amatya, Bhasker; Judson, Rodney; Truesdale, Melinda; Reinhardt, Jan D; Uddin, Taslim; Xiong, Xiang-Hu; Khan, Fary
ABSTRACT: This review aim to provide an overview of recommendations and quality of existing clinical practice guidelines (CPGs) for the management of traumatic brain injury (TBI) from the rehabilitation perspective. Comprehensive literature search, including health databases, CPG clearinghouse/developer websites, and grey literature using Internet search engines up to September 2017. All TBI CPGs published in the last decade were selected if their scope included management of TBI, systematic methods for evidence search, clear defined recommendations, and supporting evidence for rehabilitation interventions. Three authors independently critically appraised the quality of included CPGs using the Appraisal of Guidelines, Research, and Evaluation II (AGREE II) Instrument. Four of 13 potential CPGs met the inclusion criteria. Despite variation in scope, target population, size, and guideline development processes, all four CPGs assessed were good quality (AGREE score of 5–7/7). Key rehabilitation recommendations included education, physical rehabilitation, integrated computer-based management, repetitive task-specific practice in daily living activities, safe equipment usage, cognitive/behavioral feedback, compensatory memory/visual strategies, swallowing/communication, and psychological input for TBI survivors. In conclusion, although rehabilitation is an integral component in TBI management, many published CPGs do not include rehabilitation. These CPGs, however, recommend comprehensive, flexible coordinated multidisciplinary care and appropriate follow-up, education, and support for patients with TBI (and carers).